A victim's claim of being raped is neither a confession to Zina nor Committing qadhf (making false accusation of zina) - Mohd Noor, Azman (Walter de Gruyter GmbH & Co. KG, 2011)
Sexual assault leaves the victims with unbearable emotional pain from the experience. The unwanted aggression against their freewill causes them to suffer physically and mentally. On top of that, they also have to fight to be treated fairly and respectfully during their court trials. There has been some controversy regarding rape prosecution in the Islamic legal system. The reason for this controversy is that the rape victim would usually be either charged with zina because of her confession, or committing qadhf, as a result of her failure to provide four male eyewitnesses. This paper aims at investigating the fundamental legal rights of rape victims who complain of being raped, to be defended fairly, and to get exemption from punishment as provided in Islamic law. This paper also seeks to investigate the admissibility of the individual testimony of the victim against the rapist. This paper suggests that proving rape is not similar to proving zina, because a rape victim who lodges a report or complains of her ordeal of being raped should not be treated the same as a person who confesses to zina. Proving rape is also different from accusing the rapist with committing zina (qadhf). This study will explore opinions and arguments of classical Muslim scholars of Islamic jurisprudence from various schools of thought